Decompression of a Dentigerous Cyst Treatment in Mixed Dentition: A Case Report with 5 Years Follow-Up - Antoine Berberi; Georges Aad; Marise Nassar; Gwenaëlle Maalouf; Nabih Nader (Case Reports in Dentistry)
Among developmental odontogenic cysts, the dentigerous type is the second most prevailing one. It is a benign intraosseous lesion commonly affecting the mandibular region. Dentigerous cysts present a high prevalence in children as they can be caused by the eruption of permanent teeth or the infection of deciduous ones. The adopted treatment modalities include enucleation (cystectomy), marsupialization, and decompression. Decompression maintains communication between the cyst and the oral medium through a sutured fixed device, namely an acrylic stent or a pretrimmed disposable suction tube. In the mixed dentition, the extraction of the affected primary teeth and the decompression approach is recommended, especially since children and parents are more tolerant of conservative treatments. We report in this study, a case of a 9-year-old boy complaining of a painful swelling in the left mandibular region. Intraoral and radiological examination revealed an expansion of the buccal and lingual cortical plates associated with teeth #73, #74, and #75 and a well-limited, unilocular radiolucent image extending from the distal aspect of tooth #31 to the mesial aspect of tooth #36 involving the crowns of the unerupted teeth #33, #34, and #35. The preliminary diagnosis was in favor of a dentigerous cyst. The treatment was to extract the deciduous teeth and to use a sterile tube for decompression. The patient was followed up for 5 years, a complete remission of the cyst was observed and the teeth #33, #34, and #35 re-erupted normally on the mandibular arch.